Ensuring Energy Security: A Regional Aspect - Tatyana TKACHEVA; Liubov AFANASYEVA; Ivan AFANASEV; Elkhana DOROSHENKO (Communications of International Proceedings, 2021)
Energy security, as the most important structural element of the overall national security of the Russian Federation, is multilevel and multifunctional (is characterized by multilevel and multifunctional nature). It is established that in the economic system of the Russian Federation the fuel and energy complex occupies an important place and plays the role of the basic infrastructure, which forms the income of the federal and regional budgets, as well as the largest customer for economic subjects. The article identifies current trends in spatial and regional development policy in the context of ensuring energy security. It is shown that an important factor of sustainable socio-economic development is the effective implementation of regional energy policy in the context of ensuring economic security. For the purpose of monitoring of maintenance of energy security and in a context of a policy of spatial and regional development the system of indicators of energy security has been specified.
Keywords: Energy Security; Economic Security; Energy Security Indicators; Energy Policy Of The Region.